The first record of the water mite genus Ljania Thor, 1898 (Acari, Hydrachnidiae, Aturidae) from China, with description of two new species - Ao, Min; Yi, Tian-Ci; Guo, Jian-Jun (Zootaxa, 2021)
This is the first record of the genus Ljania Thor, 1898 (Axonopsinae, Aturidae, Hydrachnidiae, Acari) from China. Two new species, Ljania jini sp. nov. and Ljania guangxiensis sp. nov., are described from Guangxi Province, P. R. China. The new detections bring the total number of Chinese aturid mites to eleven species, representing seven genera.